Rapid removal of diclofenac in aqueous solution by soluble Mn(III) (aq) generated in a novel Electro-activated carbon fiber-permanganate (E-ACF-PM) process. (15th November 2019) - Zhu, Yunhua; Zhao, Chun; Liang, Jialiang; Shang, Ran; Zhu, Xuanmo; Ding, Lei; Deng, Huiping; Zheng, Huaili; Strathmann, Timothy J.
Abstract: Electrolysis and permanganate (PM) oxidation are two commonly used technologies for water treatment. However, they are often handicapped by their slow reaction rates. To improve the removal efficiency of refractory contaminants, we combined electrolysis with PM using an activated carbon fiber (ACF) as cathode (E-ACF-PM) for the first time to treat diclofenac (DCF) in aqueous solution. Up to 90% DCF was removed in 5 min by E-ACF-PM process. In comparison, only 3.95 and 27.35% of DCF was removed by individual electrolysis and PM oxidation at the same time, respectively. Acidic condition was more conducive to DCF removal. Surprisingly, soluble Mn(III) ( aq) formed on the surface of ACF was demonstrated as the principal oxidizing agent in E-ACF-PM process. Further studies showed that all three components (electrolysis + ACF + PM) were necessary to facilitate the heterogeneous generation of reactive Mn(III) ( aq) . Moreover, SEM images and XPS spectra of ACF before and after treatment revealed that the morphologies and elemental compositions of reacted ACF were nearly unchanged during the E-ACF-PM process. ACF can be remained active and utilized to the rapid degradation of DCF in E-ACF-PM process even after reused for 20 times. Therefore, the E-ACF-PM process may provide a novel and effective alternative on the generation of reactive Mn(III) ( aq) in situ for water treatment by green electrochemical reactions. Graphical abstract: Image 1 Highlights: A novel synergistic technology coupling electrolysis and permanganate (PM) was developed. DCF can be rapidly removed in E-ACF-PM process from raw water. Mn(III) formed on the ACF cathode played a key role in DCF degradation. All three components (electrolysis + ACF + PM) were necessary to facilitate the heterogeneous generation of reactive Mn(III). The recycled ACF for 20 times in E-ACF-PM process still had a satisfactory efficiency.